2003
DOI: 10.1039/b210900j
|View full text |Cite
|
Sign up to set email alerts
|

Thermal evolution of amorphous tricalcium phosphate

Abstract: Amorphous calcium phosphate (ACP) is one of the major components of biological mineralisation and plays a crucial role in several biomaterials. However, due to their instability, the thermochemical characteristics of ACP and of the derived metastable phases are still unknown. The thermal transformations affecting ACP, with a Ca/P atomic ratio close to 1.50, were studied in the range 373-1173 K. The samples were examined by X-ray diffraction, FTIR spectroscopy and BET measurements. The thermal behaviour was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 28 publications
5
66
2
Order By: Relevance
“…41 These may be attributed to the difference in the short range structure of ACP during precipitatation. The difference in aggregation/assembly of Ca polyhedron and P polyhedron or combination of structure cluster [(Ca 9 (PO 4 ) 6 or Ca 3 (PO 4 ) 2 )] in ACP lead to different short range structures.…”
Section: Synthesis Of A-tcp/ha Powdersmentioning
confidence: 98%
“…41 These may be attributed to the difference in the short range structure of ACP during precipitatation. The difference in aggregation/assembly of Ca polyhedron and P polyhedron or combination of structure cluster [(Ca 9 (PO 4 ) 6 or Ca 3 (PO 4 ) 2 )] in ACP lead to different short range structures.…”
Section: Synthesis Of A-tcp/ha Powdersmentioning
confidence: 98%
“…Amorphous calcium phosphate (ACP) has a similar structural unit to that in apatite, 1 it can act as an important intermediate product for in vitro and in vivo apatite formation. 2,3 The disordered structure makes ACP have high reactivity with body fluid to cause large dissolubility and fast apatite reprecipitation.…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous environment, by high ionic interaction, ACPs show apatite-like recrystallization. The physiological pH induces this crystallization (Somrani et al 2003;Combes and Rey 2010). Crystalline calcium phosphate biomaterials show higher thermal stability than natural and amorphous ones.…”
Section: Introductionmentioning
confidence: 99%
“…The ACPSs showed better bioactivity than crystal calcium phosphates (Brunner et al 2007b;He et al 2013). According to the study, for the higher surface area, smaller particle-sized amorphous materials showed better osteogenic differentiation on seeded cells (Somrani et al 2003;Brunner et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation